Novel 2019 coronavirus infection in children - Llaque Quiroz, Patricia Beatriz (2020)
COVID-19 is rarely reported in children and they are mildly affected in most cases. The most common clinical presentation of COVID-19 is cough, fever and sore throat; severe cases show tachypnea. The course of the disease is from one to two weeks. Laboratory findings are nonspecific; lymphopenia, elevation of C-reactive protein and procalcitonin have been described. Early chest X-ray is usually normal, and the most common tomographic findings are consolidations with halo, ground-glass opacities and tiny nodules which mainly affects subpleural areas. Management of the disease is supportive; in severe cases, it should be focused on respiratory support. It is recommended to limit the handling of respiratory secretions and to follow the same preventive measures provided to adults.